A scientometric analysis of Indian research output in medicine during 1999–2008 - Gupta, B. M. (Medknow Publications & Media Pvt Ltd, 2011)
OBJECTIVE: This study analyzes the research activities of India in medicine during 1999–2008, based on the total publication output, its growth rate, quality of papers published and rank of India in the global context. Patterns of international collaborative research output and the major partner countries of India are also discussed. This study also evaluates the research performance of different types of Indian medical colleges, hospitals, research institutes, universities and research foundations and the characteristics of published literature in Indian and foreign journals. It also analyzes the medical research output by disease and organs. MATERIALS AND METHODS: The publication data on medicine has been retrieved by using SCOPUS database. RESULTS: India holds 12th rank among the productive countries in medicine research consisting of 65,745 papers with a global publication share of 1.59% and registering a growth rate of 76.68% for the papers published during 1999–2003 to 2004–2008. CONCLUSION: High quality research in India is grossly inadequate and requires strategic planning, investment and resource support. There is also a need to improve the existing medical education system, which should foster research culture.